Frontal lobe epilepsy and mild malformation with oligodendroglial hyperplasia: Further observations on electroclinical and imaging phenotypes, and surgical perspectives - Garganis, Kyriakos; Gkiatis, Kostakis; Maletic, Jelena; Harushukuri, Jean; Kondylidis, Nikolaos; Dinopoulos, Argiris; Vorgia, Pelagia; Coras, Roland; Blümcke, Ingmar; Zountsas, Basilios (Epileptic Disorders, 2023)
Objective: Mild malformation with oligodendroglial hyperplasia (MOGHE) is a recently described clinicopathologic entity, associated with drug-resistant epilepsy and extensive epileptogenic networks. Knowledge is accumulating about particular electroclinical phenotypes, correlations with imaging, and potential prognostic significance for surgical outcomes. The study adds relevant information by documenting the presence of a hyperkinetic frontal lobe seizure phenotype in adolescents and an epileptic encephalopathy phenotype in young children. Methods: Five cases were subjected to a structured presurgical evaluation protocol, including EEG-FMRI, chronic and acute invasive EEG, subjected to frontal lobe surgery with postoperative follow-up between 15 months and 7 years. Results: In the two adult cases, surface EEG demonstrated lateralized widespread frontal lobe epileptogenicity and hyperkinetic semiological features. MRI demonstrated cortical white matter blurring and deeper white matter abnormalities. EEG-FMRI suggested concordant frontal lobe involvement. iEEG demonstrated a widespread frontal lobe epilepsy network. The three young children demonstrated a diffuse epileptic encephalopathy phenotype, with nonlocalizing, nonlateralizing surface EEG, and “spasms” as the main seizure type. MRI demonstrated extensive frontal lobe subcortical gray and white matter abnormalities, consistent with MOGHE literature for this age, while EEG-FMRI, in 2/3, demonstrated concordant frontal lobe involvement. They did not undergo chronic iEEG, and the resection was assisted by acute intraoperative ECoG. All cases were subjected to extensive frontal lobectomies with Engel class IA (2/5), IB (1/5), and IIB (2/5) outcomes. Significance: The study confirms the presence of frontal lobe epilepsy and epileptic encephalopathy phenotypes, in accordance with epilepsy phenotypes already described in MOGHE literature. Presurgical evaluation studies, including EEG-FMRI, can provide strong lateralizing and localizing evidence of the epileptogenic networks involved. All responded favorably to extensive frontal lobe resections, despite widespread epileptic activity recorded by surface and intracranial EEG pre- and postoperatively; an epileptic encephalopathy phenotype, in the first years of life, should not discourage such a resection.
CRIS-Team Scopus Importer:2023-05-19
Keywords: cortical dysplasia; EEG-fMRI; epilepsy surgery; epileptic encephalopathy; hyperkinetic seizures